GLP-1, the Gut-Brain, and Brain-Periphery Axes (The Review of Diabetic Studies, 2023)
Glucagon-like peptide 1 (GLP-1) is a gut hormone which directly binds to the GLP-1 receptor located at the surface of the pancreatic β-cells to enhance glucose-induced insulin secretion. In addition to its pancreatic effects, GLP-1 can induce metabolic actions by interacting with its receptors expressed on nerve cells in the gut and the brain. GLP-1 can also be considered as a neuropeptide synthesized by neuronal cells in the brain stem that release the peptide directly into the hypothalamus. In this environment, GLP-1 is assumed to control numerous metabolic and cardiovascular functions such as insulin secretion, glucose production and utilization, and arterial blood flow. However, the exact roles of these two locations in the regulation of glucose homeostasis are not well understood. In this review, we highlight the latest experimental data supporting the role of the gutbrain and brain-periphery axes in the control of glucose homeostasis. We also focus our attention on the relevance of βcell and brain cell targeting by gut GLP-1 for the regulation of glucose homeostasis. In addition to its action on β-cells, we find that understanding the physiological role of GLP-1 will help to develop GLP-1-based therapies to control glycemia in type 2 diabetes by triggering the gut-brain axis or the brain directly. This pleiotropic action of GLP-1 is an important concept that may help to explain the observation that, during their treatment, type 2 diabetic patients can be identified as ‘responders’ and ‘non-responders’.